Large-scale transport of PM2.5 in the lower troposphere during winter cold surges in China. Issue 1 (December 2017) - Wang, Jianjun; Zhang, Meigen; Bai, Xiaolin; Tan, Hongjian; Li, Sabrina; Liu, Jiping; Zhang, Rui; Wolters, Mark; Qin, Xiuyuan; Zhang, Miming; Lin, Hongmei; Li, Yuenan; et al.
Abstract A comprehensive investigation using the air quality network and meteorological data of China in 2015 showed that PM2.5 driven by cold surges from the ground level could travel up to 2000 km from northern to southern China within two days. Air pollution is more severe and prominent during the winter in north China due to seasonal variations in energy usage, trade wind movements, and industrial emissions. In February 2015, two cold surges traveling from north China caused a temporary increase in the concentration of PM2.5 in Shanghai. Subsequently, the concentration of PM2.5 in Xiamen increased to a high of 80 µg/m3, which is double the average PM2.5 concentration in Xiamen during the winter. This finding is a new long-range transport mechanism comparing to the well-established mechanism, with long-range transport more likely to occur in the upper troposphere than at lower levels. These observations were validated by results from the back trajectory analysis and the RAMS- CMAQ model. While wind speed was found to be a major facilitator in transporting PM2.5 from Beijing to Xiamen, more investigation is required to understand the complex relationship between wind speed and PM2.5 and how it moderates air quality in Beijing, Shanghai, and Xiamen.